2015
DOI: 10.1097/mph.0000000000000427
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Adolescents and Young Adults With Sickle Cell Disease From Pediatric to Adult Health Care

Abstract: The transition from pediatric to adult healthcare is often challenging for adolescents and young adults with sickle cell disease (SCD). Our study aimed to identify (1) measures of success for the transition to adult healthcare and (2) barriers and facilitators to this process. We interviewed 13 SCD experts and asked them about their experiences caring for adolescents and young adults with SCD. Our interview guide was developed based on Social-ecological Model of Adolescent and Young Adult Readiness to Transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 36 publications
1
51
1
Order By: Relevance
“…We incorporated previously defined metrics as our outcome measures . The primary outcome was differences in the proportion of patients who were lost to follow‐up (defined as no interaction with the clinic for more than one year) between the pre‐TN and post‐TN cohorts.…”
Section: Post‐transfer Supportmentioning
confidence: 99%
“…We incorporated previously defined metrics as our outcome measures . The primary outcome was differences in the proportion of patients who were lost to follow‐up (defined as no interaction with the clinic for more than one year) between the pre‐TN and post‐TN cohorts.…”
Section: Post‐transfer Supportmentioning
confidence: 99%
“…Patient and adult diabetes provider perspectives in T1D suggest that there is a lack of standardized and appropriate preparation of patients for adult care as well as barriers such as patient/provider reluctance to leave pediatric care . Reports from pediatric providers transitioning chronic diseases other than T1D, such as inflammatory bowel disease (IBD) and sickle cell disease, demonstrate that there is no standardization in transition care, lack of adherence to formal guidelines, and corroborate many of the barriers reported by T1D YA patients, families, and adult providers . However, it remains unclear what is actually experienced by U.S. pediatric diabetes providers.…”
Section: Introductionmentioning
confidence: 99%
“…7,34 The difficulties surrounding transitions of care are complex as well as well researched and discussed. [35][36][37][38][39][40][41] As a result of the complexities surrounding the successful transition of a marginalized population from the family-directed pediatric medical home to fragmented and patient-directed adult services, there is a higher rate of morbidity in late adolescents and young adults with SCD. 42 It has been shown that the highest rate of acute care encounters and rehospitalizations is in those 18-30 years old and not in older patients, as one would expect if the cause were increasing disease morbidity and age.…”
Section: Disease Experiencementioning
confidence: 99%